Ocular and craniofacial phenotypes in a large Brazilian family with congenital aniridia. (16th January 2014) - Fernandes‐Lima, Z.S.; Paixão‐Côrtes, V.R.; de Andrade, A.K.M.; Fernandes, A.S.; Coronado, B.N.L.; Monte Filho, H.P.; Santos, M.J.; de Omena Filho, R.L.; Biondi, F.C.; Ruiz‐Linares, A.; Ramallo, V.; Hünemeier, T.; et al.
<x xml:space="preserve">Abstract</x> Congenital aniridia is a rare genetic disorder characterized by varying degrees of iris hypoplasia that are associated with additional ocular abnormalities. More than 90% of the causal mutations identified are found in the PAX6 gene, a transcription factor of critical importance in the process of neurogenesis and ocular development. Here, we investigate clinical, molecular, and craniofacial features of a large Brazilian family with congenital aniridia. Among the 56 eyes evaluated, phenotype variation encompassed bilateral total aniridia to mild iris defects with extensive variation between eyes of the same individual. PAX6 molecular screening indicated a heterozygous splice mutation (c.141 + 1G>A). Thus, we hypothesize that this splicing event may cause variation in the expression of the wild‐type transcript, which may lead to the observed variation in phenotype. Affected individuals were more brachycephalic, even though their face height and cephalic circumference were not significantly different when compared to those of non‐affected relatives. From this, we infer that the head shape of affected subjects may also be a result of the PAX6 splice‐site mutation. Our data summarize the clinical variability associated with the ocular phenotype in a large family with aniridia, and help shed light on the role of PAX6 in neurocranial development.